Molecular characterization of the circadian clock in paediatric leukaemia patients: a prospective study protocol - Marius Ludwig; Alireza Basti; Müge Yalçin; Johannes H. Schulte; Angela Relógio (BMC Pediatrics, 2023)
Abstract Background In many organisms, including humans, the timing of cellular processes is regulated by the circadian clock. At the molecular level the core-clock consists of transcriptional-translational-feedback loops including several genes such as BMAL1, CLOCK, PERs and CRYs generating circa 24-h rhythms in the expression of about 40% of our genes across all tissues. Previously these core-clock genes have been shown to be differentially expressed in various cancers. Albeit a significant effect in treatment optimization of chemotherapy timing in paediatric acute lymphoblastic leukaemia has previously been reported, the mechanistic role played by the molecular circadian clock in acute paediatric leukaemia remains elusive. Methods To characterize the circadian clock, we will recruit patients with newly diagnosed leukaemia and collect time course saliva and blood samples, as well as a single bone marrow sample. From the blood and bone marrow samples nucleated cells will be isolated and further undergo separation into CD19+ and CD19− cells. qPCR is performed on all samples targeting the core-clock genes including BMAL1, CLOCK, PER2 and CRY1. Resulting data will be analysed for circadian rhythmicity using the RAIN algorithm and harmonic regression. Discussion To the best of our knowledge this is the first study aiming to characterize the circadian clock in a cohort of paediatric patients with acute leukaemia. In the future we hope to contribute to uncovering further vulnerabilities of cancers associated with the molecular circadian clock and in particular adjust chemotherapy accordingly, leading to more targeted toxicity, and hence decreased systemic toxicities.